2017
DOI: 10.1016/j.bodyim.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient-identified events implicated in the development of body dysmorphic disorder

Abstract: Little is known about the causes of body dysmorphic disorder (BDD), but researchers have proposed a diathesis-stress model. This study uses a patient-centered approach to identify stressful events to which patients attribute the development of their BDD symptoms. An Internetrecruited sample of 165 adults with BDD participated. A large minority of participants attributed the development of their BDD to a triggering event. Bullying experiences were the most commonly described type of event. Additionally, most ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In fact, BDD participants remember appearance related teasing as more vivid and traumatic than controls [15]. For those that attribute their BDD to a specific triggering event, teasing and bullying appears to be the most common culprit [16]. Specifically, appearance related bullying incidents of an interpersonal nature during grade and middle school were reported.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, BDD participants remember appearance related teasing as more vivid and traumatic than controls [15]. For those that attribute their BDD to a specific triggering event, teasing and bullying appears to be the most common culprit [16]. Specifically, appearance related bullying incidents of an interpersonal nature during grade and middle school were reported.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…BULLYING AND BODY DYSMORPHIC DISORDER psychosocial outcomes than BDD individuals with other triggering events, suggesting that bullying specifically is an important variable to investigate further [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Environment and life experiences may contribute to BDD, especially if they involve negative social evaluations about someone's appearance, body or self-image, or even childhood neglect or abuse. Bullying has been shown to be associated with BDD, and most episodes were interpersonal and occurred during grade school or middle school [51]. BDD symptoms were higher when adolescents self-reported more appearance teasing and higher social anxiety.…”
Section: Environment and Life Experiencesmentioning
confidence: 99%
“…In addition, some retrospective studies reported increased rates of abuse in patients with BDD compared with those in healthy men and patients with obsessive-compulsive disorder. [36][37][38] Environmental impact as a risk factor for BDD is not yet fully understood, but understanding its role will greatly help in the prevention and psychological counseling of BDD.…”
Section: Body Dysmorphic Syndrome (Penile Dysmorphic Syndrome)mentioning
confidence: 99%